1981
DOI: 10.1111/j.1476-5381.1981.tb09113.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF IMPROMIDINE (SK&F 92676) ON THE ISOLATED PAPILLARY MUSCLE OF THE GUINEA‐PIG

Abstract: Impromidine was found to have a positive inotropic effect on the isolated papillary muscle from the guinea‐pig. The dose‐response curve to impromidine was shifted to the right by cimetidine and ranitidine. Impromidine was 35 times more potent than histamine but with a maximal response of only 81% that obtained with histamine. This difference, which was statistically significant (P < 0.005), suggested that impromidine acts as a partial agonist at the histamine H2‐receptors of the papillary muscle as has been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…5]. In addition, the pA2 value of oxmetidine was higher than that of cimetidine and the pA2 value of SKF 93479 was higher than that of oxmetidine: this find ing is consistent with the observations re ported by others [6,9,13,14] on the atrium and papillary muscle of the guinea pig. two 'classical' in vitro models for the study of H2-rcceptor antagonists.…”
Section: Discussionsupporting
confidence: 81%
“…5]. In addition, the pA2 value of oxmetidine was higher than that of cimetidine and the pA2 value of SKF 93479 was higher than that of oxmetidine: this find ing is consistent with the observations re ported by others [6,9,13,14] on the atrium and papillary muscle of the guinea pig. two 'classical' in vitro models for the study of H2-rcceptor antagonists.…”
Section: Discussionsupporting
confidence: 81%
“…A striking feature of the response to impromidine was that the maximum response was significantly less than the maximum response to histamine, a feature of compounds with partial agonist activity. Previous studies have shown that impromidine elicits a similar maximum response to histamine on guinea-pig atria (Durant et al, 1978;Owen et al, 1979), although the maximum effect on the ventricle was slightly, but significantly less for impromidine than histamine as assessed by measurement of left ventricular dp/dt,,a, in isolated working hearts or in isolated, ventricular strips (Bertaccini & Coruzzi, 1981). In neither of the guinea-pig studies was the lower maximum response to impromidine on the ventricle shown to be associated with the capacity of impromidine to inhibit maximal responses to histamine, a fundamental feature of partial agonism.…”
Section: Discussionmentioning
confidence: 99%
“…Impromidine is a very potent and selective histamine H2-receptor agonist (Durant et al, 1978), which elicits increases in rate and force of contraction of guinea-pig hearts Bertaccini & Coruzzi, 1981). We have now investigated further the pharmacology of impromidine on human ventricular myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…Impromidine appears to act as a partial agonist on histamine receptors in the rat isolated uterus and stomach (Durant et al, 1978;Parsons & Sykes, 1980), the rabbit stomach (Curwain & Turner, 1981), and in the guinea-pig isolated gastric cells (Lewin, Grelac, Cheret, Rene & Bonfils, 1979) and papillary muscle (Bertaccini & Coruzzi, 1981). Histamine has been reported to be released during sympathetic nerve stimulation in the guinea-pig isolated perfused heart (Levi & Roby, 1981) and in the dog heart in situ (Karch, Ingram, Oravec & Cohen, 1977).…”
Section: Effect Of 2-(2-pyridyl)-ethylaminementioning
confidence: 99%